Unraveling adipose tissue proteomic landscapes in severe obesity: insights into metabolic complications and potential biomarkers - Hruska, Pavel; Kucera, Jan; Kuruczova, Daniela; Buzga, Marek; Pekar, Matej; Holeczy, Pavol; Potesil, David; Zdrahal, Zbynek; Bienertova-Vasku, Julie (American journal of physiology. Endocrinology and metabolism, 2023)
In this study, we aimed to comprehensively characterize the proteomic landscapes of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) in patients with severe obesity, to establish their associations with clinical characteristics, and to identify potential serum protein biomarkers indicative of tissue-specific alterations or metabolic states. We conducted a cross-sectional analysis of 32 patients with severe obesity (16 males and 16 females) of Central European descent who underwent bariatric surgery. Clinical parameters and body composition were assessed using dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance, with 15 patients diagnosed with type 2 diabetes (T2D) and 17 with hypertension. Paired SAT and VAT samples, along with serum samples, were subjected to state-of-the-art proteomics liquid chromatography-mass spectrometry (LC-MS). Our analysis identified 7,284 proteins across SAT and VAT, with 1,249 differentially expressed proteins between the tissues and 1,206 proteins identified in serum. Correlation analyses between differential protein expression and clinical traits suggest a significant role of SAT in the pathogenesis of obesity and related metabolic complications. Specifically, the SAT proteomic profile revealed marked alterations in metabolic pathways and processes contributing to tissue fibrosis and inflammation. Although we do not establish a definitive causal relationship, it appears that VAT might respond to SAT metabolic dysfunction by potentially enhancing mitochondrial activity and expanding its capacity. However, when this adaptive response is exceeded, it could possibly contribute to insulin resistance (IR) and in some cases, it may be associated with the progression to T2D. Our findings provide critical insights into the molecular foundations of SAT and VAT in obesity and may inform the development of targeted therapeutic strategies.NEW & NOTEWORTHY This study provides insights into distinct proteomic profiles of subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), and serum in patients with severe obesity and their associations with clinical traits and body composition. It underscores SAT's crucial role in obesity development and related complications, such as insulin resistance (IR) and type 2 diabetes (T2D). Our findings emphasize the importance of understanding the SAT and VAT balance in energy homeostasis, proteostasis, and the potential role of SAT capacity in the development of metabolic disorders.
Keywords: obezita; tuková tkáň; Humans; proteiny; proteomics; Insulin Resistance; Proteomics; Proteins; Intra-Abdominal Fat; subcutaneous adipose tissue; Female; type 2 diabetes; visceral adipose tissue; lidé; Biomarkers; proteomika; Diabetes Mellitus, Type 2; Obesity, Morbid; Subcutaneous Fat; ženské pohlaví; biologické markery; nitrobřišní tuk; Male; Adipose Tissue; inzulinová rezistence; morbidní obezita; Cross-Sectional Studies; Obesity; mužské pohlaví; diabetes mellitus 2. typu; obesity; průřezové studie; podkožní tuk